Aesthetic and incentive salience of cute infant faces: studies of observer sex, oral contraception and menstrual cycle. - Reiner Sprengelmeyer (Public Library of Science (PLoS), 2013)
Infant cuteness can influence adult-infant interaction and has been shown to activate reward centres in the brain. In a previous study, we found men and women to be differentially sensitive to small differences in infant facial cuteness, with reproductive hormone status as the potential underlying cause. It is unclear, however, whether reproductive hormone status impacts on the aesthetic and incentive salience of infant faces. To address this question, we conducted two interlinked studies. We used static images of the same smiling and neutral-looking infant faces in both a rating task, in which participants had to rate the cuteness of infant faces (aesthetic salience - 'liking'), and a key-press task, in which participants could prolong or shorten viewing time of infant faces by rapid alternating key-presses (incentive salience - 'wanting'). In a first study, we compared the performance of men, women who are taking oral contraceptives, and regularly cycling women. In this study, we found a significant correlation between cuteness ratings within and between groups, which implies that participants had the same concept of cuteness. Cuteness ratings and effort to look at faces was linked regardless of sex and reproductive hormone status, in that cute faces were looked at for longer than less cute faces. A happy facial expression contributed only marginally to the incentive salience of the face. To explore the potential impact of reproductive hormone status in more detail, we followed a subset of regularly cycling women during the menstrual, follicular and luteal phases of their cycle. The aesthetic and incentive salience of infant faces did not change across the menstrual cycle. Our findings suggest that reproductive hormone status does not modulate the aesthetic and incentive value of infant faces.